Growth Performance Evaluation of Doyogena Sheep under Community Based Breeding Scheme, Doyogena Woreda Southern Ethiopia (Global Journal of Science Frontier Research, 2021)
The aim of this study was to evaluate the growth performance of Doyogena sheep under community based breeding scheme in Doyogena district. The district was chosen purposively due to the existence of sheep breeding cooperatives. Data on birth weight (BW), 90-day weaning weight (WW) and six-month weight of 584 lambs born in Doyogena community based sheep breeding cooperatives over the period of 2013-2015 were collected and used for this study. Pre-and post weaning average daily gain were also estimated. Data were subjected to analysis of variance using the GLM procedure of SPSS. The overall least square mean weight of Doyogena sheep at birth, at 3and 6 months of age were 2.9, 12.1 and 18.9 kg, respectively. The pre-and postweaning average daily weight gains were 103.6 and 67.3g/day, respectively.
Keywords: breeding; community based; lamb; growth performance; Doyogena sheep